2004
DOI: 10.1093/pcp/pch050
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple-Stress Responsive Plastid Sigma Factor, SIG5, Directs Activation of the psbD Blue Light-Responsive Promoter (BLRP) in Arabidopsis thaliana

Abstract: Transcription in higher plant plastids is performed by two types of RNA polymerases called NEP and PEP, and expression of photosynthesis genes in chloroplasts is largely dependent on PEP, a eubacteria-type multi-subunit enzyme. The transcription specificity of PEP is modulated by six nuclear-encoded sigma factors (SIG1 to SIG6) in Arabidopsis thaliana. Here, we show that one of the six sigma factors, SIG5, is induced under various stress conditions, such as high light, low temperature, high salt and high osmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
162
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(175 citation statements)
references
References 66 publications
13
162
0
Order By: Relevance
“…This assumption was first supported by the finding that a nuclear encoded sigma factor gene, SIG5, is specifically induced by blue light irradiation in Arabidopsis, 66) and confirmed by the observation that BLRP lost activity in mutants deficient in the SIG5 gene. 67,68) Tsunoyama et al also found that a transient expression of SIG5 in dark-adapted protoplasts elevated psbD transcription activity. 67) Hence direct involvement of SIG5 in the BLRP activation was strongly suggested.…”
Section: Sig5 Is a Stress-responsive Sigma Factor In Chloroplast mentioning
confidence: 96%
“…This assumption was first supported by the finding that a nuclear encoded sigma factor gene, SIG5, is specifically induced by blue light irradiation in Arabidopsis, 66) and confirmed by the observation that BLRP lost activity in mutants deficient in the SIG5 gene. 67,68) Tsunoyama et al also found that a transient expression of SIG5 in dark-adapted protoplasts elevated psbD transcription activity. 67) Hence direct involvement of SIG5 in the BLRP activation was strongly suggested.…”
Section: Sig5 Is a Stress-responsive Sigma Factor In Chloroplast mentioning
confidence: 96%
“…The photoreceptors cryptochromes and phytochrome A are responsible for light sensing and the control of nuclear responses (Thum et al, 2001). The command reaches the plastids through the action of AtSig5, since this sigma factor specifically is expressed in response to light , in a very rapid manner (Dillon, Bögre and López-Juez, unpublished observations) and also responds to a number of stresses that in nature compound the propensity to photodamage (Nagashima et al, 2004). The control is therefore elegantly simple: a photoreceptor with action in the cell nucleus activates the transcription of a specific sigma factor and this factor, targeted to the chloroplast, acts as a co-factor of the plastid RNA polymerase and activates the transcription of a plastidencoded gene (Fig.…”
Section: The Control Of Plastid Gene Transcriptionmentioning
confidence: 99%
“…Whereas basic sigma functions have been tested to a large extent using heterologous in vitro systems with authentic plastid or bacterially expressed sigma proteins and Escherichia coli RNA polymerase (Hakimi et al, 2000;Hanaoka et al, 2003;Homann and Link, 2003), the availability of Arabidopsis sigma mutant lines has facilitated functional studies in vivo (Hanaoka et al, 2003;Privat et al, 2003;Nagashima et al, 2004;Tsunoyama et al, 2004;Favory et al, 2005;Ishizaki et al, 2005). Here, we investigate an Arabidopsis knockout line with a Sig6 mutant allele (Rosso et al, 2003) that reveals a strong developmental stagespecific (albino) phenotype and characteristic changes in plastid gene expression.…”
mentioning
confidence: 99%